Effect of Atrial Fibrillation on the Risk of New-onset Myocardial Infarction in Hypertensive Population - YUE Bocheng, HOU Qiqi, HAN Quanle, YANG Bo, WU Zheng, WU Jianmei, CHEN Shuohua, WU Shouling, LI Kangbo (Zhongguo quanke yixue, 2023)
Background Global population epidemiology research shows that by 2019, there were 1.28 billion hypertensive patients, and about 59.7 million patients with atrial fibrillation (AF) worldwide. Hypertension greatly increases the risk of AF. And in older hypertensive patients, the incidence of AF will be higher than 60%. Moreover, AF increases the risk of ischemic stroke, heart failure, myocardial infarction, chronic kidney disease and dementia. However, there are few studies on whether AF increases the risk of new-onset myocardial infarction, and whether the risk interacts with age is still unclear in large hypertensive populations. Objective To examine whether AF increases the risk of new-onset myocardial infarction in hypertensive patients. Methods Individuals with hypertension were selected as subjects from the employees of Kailuan Group who underwent the medical check-up in Tangshan Gongren Hospital and Kailuan General Hospital from June 2006 to October 2007. General data and laboratory test results of subjects were collected. And all of them were regularly followed up until 2020-12-31. The endpoint event was new-onset myocardial infarction. The finally enrolled cases (n=42 833) included 270 with AF diagnosed by baseline ECG (AF group) and 42 563 without (non-AF group) . The cumulative incidence of myocardial infarction was calculated by the life table method. The survival curve for the cumulative incidence of new-onset myocardial infarction was plotted by Kaplan-Meier method. The difference of the cumulative incidence of myocardial infarction between AF and non-AF groups was compared by Log-rank test. Multivariate Cox proportional hazards regression model was used to investigate the effect of AF on new-onset myocardial infarction in hypertension. Results AF group had greater mean age, and lower mean levels of diastolic blood pressure, total cholesterol, triglyceride, low-density lipoprotein cholesterol than non-AF group (P<0.05) . There were also statistically differences in the incidence of myocardial infarction and cumulative incidence of new-onset myocardial infarction between the two groups (P<0.05) . After age-stratification, it was found that the differences in the incidence of new-onset myocardial infarction and cumulative incidence of myocardial infarction were statistically significant between those aged ≤60 years with AF and without AF (P<0.05) , but were insignificant between those aged > 60 years with and without AF (P>0.05) . Adjusted multivariate Cox proportional hazards regression analysis showed that AF was a risk factor for new-onset myocardial infarction in hypertensive population〔HR=2.89, 95%CI (1.74, 4.82) , P<0.01〕, and also in hypertensive population aged ≤60 years old〔HR=4.72, 95%CI (2.11, 10.56) , P<0.01〕. Conclusion AF is a risk factor for new-onset myocardial infarction in hypertensive population, especially in those ≤60 years old. Active control of blood pressure and treatment of AF are important prevention and treatment measures for new-onset myocardial infarction.